Digital navigation of energy–structure–function maps for hydrogen-bonded porous molecular crystals - Chengxi Zhao (Nature Portfolio, 2021)
Energy–structure–function (ESF) maps can facilitate functional materials discovery. Here the authors provide a protocol for the digital navigation of ESF maps, as demonstrated for hydrogen-bonded organic frameworks constructed from triptycene- and spiro-biphenyl-based molecular building block.